Agustian, Daden Metode Pelaksanaan Pekerjaan Strauss Pile Proyek Gedung Kejaksaan Negeri Majalengka - Agustian, Daden; Eka Juliar (Universitas Majalengka, 2024)
Construction work is divided into different scopes of work, including structural, architectural, MEP and others. The structure is a means that functions to distribute live loads and dead loads into the ground. One part of the structure is the foundation which is a part of the building construction whose task is to place and transmit the load of the upper part of the building to the subgrade. The selection of the type of foundation structure is carried out by taking into account the condition of the soil, the limitations imposed by the structure above it, the limitations of the surrounding environment, the cost and time of carrying out the work. For example, the Majalengka District Attorney's building construction project uses a Strauss Pile foundation as the lower. Strauss foundation is a type of foundation that is used to carry loads when hard soil that has a strong bearing capacity is located very deep from the ground surface. In this project, the implementation of the Strauss Pile work refers to the provisions that must have the ASTM D 1143-81 standard regarding static compressive loading, using concrete quality K300 and reinforcing steel Ø ≥ 10 BJTD 40 and Ø≤ 10 BJTP 24. The work process starts from a series of works Preparation includes administrative equipment, land clearing and measurements, then carrying out work starting from drilling using a mini crane auger to casting, and finally testing as a technical report.